Efficient alkaline seawater oxidation by a three-dimensional core-shell dendritic NiCo@NiFe layered double hydroxide electrode. (October 2022) - Zhang, Fanghao; Liu, Yifei; Wu, Libo; Ning, Minghui; Song, Shaowei; Xiao, Xin; Hadjiev, Viktor G.; Fan, Donglei Emma; Wang, Dezhi; Yu, Luo; Chen, Shuo; Ren, Zhifeng
Abstract: Seawater electrolysis for hydrogen generation has received increasing attention recently due to the scarcity of freshwater and the additional prospect of seawater desalination. The development of non-noble-metal-based oxygen evolution reaction (OER) electrocatalysts with high catalytic activity, long-term durability, and high OER selectivity is crucial for large-scale seawater electrolysis but remains a significant challenge. Here we develop a three-dimensional core-shell dendritic catalyst by vertically growing NiFe layered double hydroxide (LDH) nanosheets on dendritic NiCo branches (denoted as NiCo@NiFe LDH). The dendritic NiCo@NiFe LDH is highly active and stable in alkaline seawater due to its large surface area, fast charge transfer and effective mass transfer, and excellent corrosion resistance. It requires only a small overpotential of 222 mV to achieve current densities of 100 mA cm −2 in 1 M KOH seawater. To deliver a large current density of 500 mA cm −2, the NiCo@NiFe LDH catalyst requires a record-low overpotential of 266 mV. The nearly 100% OER Faradaic efficiency and the absence of ClO − in the electrolyte following seawater electrolysis indicate the high OER selectivity of our catalyst. The stability of NiCo@NiFe LDH in seawater is proven by its small overpotential fluctuation at a constant current density of 500 mA cm −2 over 100 h. Graphical abstract: Image 1 Highlights: A large-surface-area 3D core-shell NiCo@NiFe LDH electrode is synthesized. Low overpotential of 266 mV at 500 mA cm –2 in alkaline natural seawater is obtained. The importance of a large surface area in seawater electrolysis has been investigated.